Contribution of machining to the fatigue behaviour of metal matrix composites (MMCs) of varying reinforcement size. (September 2017) - Pramanik, A.; Islam, M.N.; Davies, I.J.; Boswell, B.; Dong, Y.; Basak, A.K.; Uddin, M.S.; Dixit, A.R.; Chattopadhyaya, S.
Highlights: The presence and size of particles affected the fatigue life significantly. Balance of strain hardening and heat generation reduce feed and speed effects. The interactions of different parameters significantly affect fatigue life. Smaller or no particles induces a complete separation of failed samples. Cracks are arrested or deflected by the bigger reinforced particles. Abstract: The high cycle constant stress amplitude fatigue performance of metal matrix composite (MMC) components machined by a milling process was investigated in this study as a function of machining speed, feed rate and reinforcement particle size. The presence of reinforcement and particle size were found to be the most influential factors that affected the fatigue life. In contrast to this, the effect of feed and speed on tool-particle interaction, strain hardening and heat generation during milling of MMCs were balanced in such a way that the contributions of feed and speed on fatigue life were negligible. The interactions of different parameters contributed significantly to the fatigue life which indicated that the modelling of fatigue life based on these three parameters was relatively complex. The fatigue life of the machined MMC samples increased with decreasing particle size and increasing feed. However, the fatigue life was not influenced by speed variation. The presence of smaller or no particles induced a complete separation of failed samples, in contrast to that of specimens containing larger reinforcing particles where crack growth was arrested or deflected by the reinforcing particles.